Hollywood and the O.K. Corral portrayals of the gunfight and Wyatt Earp - Blake, Michael Francis (McFarland, 2007)
"This volume examines eight movies of the legendary gunfight, produced from 1939 to 1994, and each use Wyatt Earp and other real-life characters as their sources. The work focuses on the filmmakers' treatment of the history and the skill with which each balances fact with the necessity of entertainment. Period photographs are also included"--Provided by publisher.
"This volume examines eight movies of the legendary gunfight, produced from 1939 to 1994, and each use Wyatt Earp and other real-life characters as their sources. The work focuses on the filmmakers' treatment of the history and the skill with which each balances fact with the necessity of entertainment. Period photographs are also included"--Provided by publisher.
Includes bibliographical references and index
Keywords: Earp, Morgan -- 1851-1882 -- In motion pictures; Earp, Wyatt -- 1848-1929 -- In motion pictures; Holliday, John Henry -- 1851-1887 -- In motion pictures; Earp, Wyatt -- 1848-1929; Holliday, John Henry -- 1851-1887; Western films -- United States -- History and criticism; Western -- Film; USA